Down-regulation of lncRNA-NEF indicates poor prognosis in intrahepatic cholangiocarcinoma. Issue 5 (21st May 2019) - Liang, Zhanqiang; Zhu, Bingshuai; Meng, Dongdong; Shen, Xiwen; Li, Xuemin; Wang, Zhongzhen; Li, Liantao
Abstract : LncRNA-NEF is a tumor suppressor lncRNA in liver cancer. The present study aimed to investigate the role of lncRNA-NEF in intrahepatic cholangiocarcinoma (IHCC), which is second most common type of primary cancer of the hepatobiliary system that causes high mortality rate. In the present study we found that lncRNA-NEF was down-regulated, while Runt-related transcription factor 1 (RUNX1) was up-regulated in tumor tissues than in adjacent healthy tissues of IHCC patients. Expression levels of lncRNA-NEF and RUNX1 were significantly and reversely correlated in tumor tissues but not in adjacent healthy tissues. Plasma levels of lncRNA-NEF were significantly lower in IHCC patients than in healthy controls. Down-regulation of lncRNA-NEF effectively distinguished stage I and II IHCC patients from healthy controls. Patients were followed up for 5 years, patients with high plasma levels of lncRNA-NEF showed significantly better survival conditions compared with patients with low expression levels of lncRNA-NEF. LncRNA-NEF overexpression led to inhibited expression of RUNX1 in cells of IHCC cell lines and inhibited cancer cell migration and invasion. In contrast, RUNX1 overexpression showed no significant effects on lncRNA-NEF expression, but attenuated the effects of lncRNA-NEF overexpression on cancer cell migration and invasion. We therefore concluded that lncRNA-NEF participated in IHCC possibly by interacting with RUNX1.